2000
DOI: 10.2105/ajph.90.5.768
|View full text |Cite
|
Sign up to set email alerts
|

Cigarettes and suicide: a prospective study of 50,000 men

Abstract: A B S T R A C TObjectives. This study examined the relation between smoking and suicide, controlling for various confounders.Methods. More than 50 000 predominantly White, middle-aged and elderly male health professionals were followed up prospectively with biennial questionnaires from 1986 through 1994. The primary end point was suicide. Characteristics controlled for included age, marital status, body mass index, physical activity, alcohol intake, coffee consumption, and history of cancer.Results. Eighty-two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(23 citation statements)
references
References 80 publications
(74 reference statements)
2
21
0
Order By: Relevance
“…2000; Breslau et al 2005; Yaworski et al 2011) but other have not (Hemmingsson and Kriebel 2003; Kessler et al 2007; Boden et al 2008). However, two of these studies were cross-sectional (Kessler et al 2007; Yaworski et al 2011) and most of the prospective cohorts did not adjust for psychiatric disorders (Hemenway et al 1993; Tverdal et al 1993; Doll et al 1994; Leistikow et al 2000; Miller et al 2000a; Miller et al 2000b; Iwasaki et al 2005). Even if several cohort studies have found a positive monotonic association between cigarette smoking and suicide or suicidal behavior, smoking was assessed only at the cohort inception and not updated during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2000; Breslau et al 2005; Yaworski et al 2011) but other have not (Hemmingsson and Kriebel 2003; Kessler et al 2007; Boden et al 2008). However, two of these studies were cross-sectional (Kessler et al 2007; Yaworski et al 2011) and most of the prospective cohorts did not adjust for psychiatric disorders (Hemenway et al 1993; Tverdal et al 1993; Doll et al 1994; Leistikow et al 2000; Miller et al 2000a; Miller et al 2000b; Iwasaki et al 2005). Even if several cohort studies have found a positive monotonic association between cigarette smoking and suicide or suicidal behavior, smoking was assessed only at the cohort inception and not updated during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore accessed data from three large U.S. cohorts in which cigarette smoking was assessed every two years to investigate prospectively and over a long follow-up period the association between smoking and quitting smoking and risk of deaths from suicide. The present work represents an extension of a previous brief report in the NHS (Hemenway et al 1993) and a report based on only 8 years of follow-up in the HPFS (Miller et al. 2000b).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The time scale for the analysis was then measured in months since the start of the current questionnaire cycle. We also adjusted our estimates for baseline occupational category (27, 28) and the following time-updated variables: employment status (29); smoking status (30); alcohol intake (31); caffeine intake (32); antidepressant medication use (13, 33); body mass index (34, 35); self-report of a routine physical examination within the previous 2 years; weekly physical activity (36); and history of hypertension, diabetes, hypercholesterolemia, or renal failure (37, 38). To evaluate for departures from the proportional hazards assumption, we used likelihood ratio tests comparing models with and without the interaction terms of age by the specific exposures of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Current cigarette smoking was associated with about a two-fold relative risk for suicide in SCCS participants. Perhaps no risk factor for suicide has been examined more extensively than cigarette smoking, and a direct relation between smoking and suicide has been observed in most studies [9] [14] . The explanation for the association between cigarette smoking and suicide risk is unknown; it has been suggested that cigarette smoking may be a marker for stress or psychiatric problems, and residual confounding with alcohol or drug abuse is possible, but a direct role of cigarette smoking on brain levels of serotonin or monoamine oxidases has not been ruled out [10] , [14] , [29] .…”
Section: Discussionmentioning
confidence: 99%